Relapsed acute lymphoblastic leukaemia after allogeneic stem cell transplantation: a therapeutic dilemma challenging the armamentarium of immunotherapies currently available (case reports). (May 2022) - Poyer, Fiona; Füreder, Anna; Holter, Wolfgang; Peters, Christina; Boztug, Heidrun; Dworzak, Michael; Engstler, Gernot; Friesenbichler, Waltraud; Köhrer, Stefan; Lüftinger, Roswitha; Ronceray, Leila; Witt, Volker; et al.
While survival rates in paediatric acute lymphoblastic leukaemia (ALL) nowadays exceed 90%, systemic ALL relapse, especially after haemopoietic stem cell transplantation (HSCT), is associated with a poor outcome. As there is currently no standardized treatment for this situation, individualized treatment is often pursued. Exemplified by two clinical scenarios, the aim of this article is to highlight the challenge for treating physicians to find a customized treatment strategy integrating the role of conventional chemotherapy, immunotherapeutic approaches and second allogeneic HSCT. Case 1 describes a 2-year-old girl with an early isolated bone marrow relapse of an infant KMT2A -rearranged B-cell precursor ALL after allogeneic HSCT. After bridging chemotherapy and lymphodepleting chemotherapy, chimeric antigen receptor (CAR) T-cells (tisagenlecleucel) were administered for remission induction, followed by a second HSCT from the 9/10 human leukocyte antigen (HLA)-matched mother. Case 2 describes a 16-year-old girl with a late, isolated bone marrow relapse of B-cell precursor ALL after allogeneic HSCT who experienced severe treatment toxicities including stage IV renal insufficiency. After dose-reduced bridging chemotherapy, CAR T-cells (tisagenlecleucel) were administered for remission induction despite a CD19 - clone without prior lymphodepletion due to enhanced persisting toxicity. This was followed by a second allogeneic HSCT from the haploidentical mother. While patient 2 relapsed around Day + 180 after the second HSCT, patient 1 is still in complete remission >360 days after the second HSCT. Both cases demonstrate the challenges associated with systemic ALL relapse after first allogeneic HSCT, including chemotherapy-resistant disease and persisting organ damage inflicted by previous therapy. Immunotherapeutic approaches, such as CAR T-cells, can induce remission and enable a second allogeneic HSCT. However, optimal therapy for systemic ALL relapse after first HSCT remains to be defined.